Analisis Perbandingan Konsep Dasar dan Urgensi Evaluasi Pembelajaran Bahasa Arab - Muhammad Rahmat Alimin; Herdah Herdah (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Evaluation is an important component in the Arabic language learning process because it functions to determine the level of students' achievement in reaching learning objectives. In educational practice, the terms measurement, assessment, and evaluation are often used interchangeably, even though they have different meanings in terms of concept, function, and scope. This article aims to analyze the fundamental differences between measurement, assessment, and evaluation and to examine the urgency of their application in Arabic language learning. The method used in this study is a literature study by reviewing various books and scientific journals related to educational evaluation. The results of the study show that measurement focuses on collecting data in the form of numerical scores, assessment is the process of interpreting the results of measurement, while evaluation is a broader process used to determine the effectiveness of a learning program. The application of these three concepts can be found in the four Arabic language skills: listening (istima’), speaking (kalam), reading (qira’ah), and writing (kitabah). In addition, a good evaluation system should consider the principles of objectivity, validity, reliability, and fairness so that the results can accurately reflect students' abilities. Therefore, a proper understanding of measurement, assessment, and evaluation is essential for developing an effective and quality evaluation system in Arabic language learning.